2010
DOI: 10.1103/physrevlett.105.233903
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Light Guiding in Ion-Implanted Diamond

Abstract: A fine control of the variation of the refractive index as a function of structural damage is essential in the fabrication of diamond-based optical and photonic devices. We report here about the variation of the real part of the refractive index at λ = 632.8 nm in high-quality single-crystal diamond damaged with 2 and 3 MeV protons at low-medium fluences (10 13 -10 17 ions cm). After implanting the samples in 125 × 125 μm 2 areas with a raster scanning ion microbeam, the variation of optical thickness of the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…The propagation loss can be attributed to scattering and absorption from the sp 2 bonded carbon within the laser written tracks. It has been shown that fabrication of diamond using heavy ion implantation can lead to structural modifications with a smooth modulation of the real part of the refractive index 17,39 . In this study, we were unable to induce such Type I modifications, but utilizing different pulse repetition rates of the laser might potentially give access to different fabrication regimes where this becomes possible.…”
Section: Arxiv:160600170v2 [Physicsoptics] 28 Jul 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation loss can be attributed to scattering and absorption from the sp 2 bonded carbon within the laser written tracks. It has been shown that fabrication of diamond using heavy ion implantation can lead to structural modifications with a smooth modulation of the real part of the refractive index 17,39 . In this study, we were unable to induce such Type I modifications, but utilizing different pulse repetition rates of the laser might potentially give access to different fabrication regimes where this becomes possible.…”
Section: Arxiv:160600170v2 [Physicsoptics] 28 Jul 2016mentioning
confidence: 99%
“…Elegant nanobeam waveguides have recently been demonstrated through either angled 15 or undercut RIE etching 16 . Alternatively, direct ion microbeam writing has been used to create shallow subsurface multimode waveguides 17 . All of these approaches are constrained to the diamond surface, require extensive material processing to the potential detriment of the diamond and are difficult to interface with optical fibers.…”
mentioning
confidence: 99%
“…With the aim of exploiting the above-mentioned attracting properties, several diamond micro-fabrication methods are under study [7][8][9][10][11][12], promising to offer a viable path towards the integration of monolithic photonic devices while exploiting the broad-band transparency and high refractive index of this material. Such methods are often based on ionbeam microfabrication strategies [7,9,11,12]: possible variations of the refractive index due to structural damage during the device fabrication process must be accurately predicted to properly design the devices of interest . Moreover, with the aim of fabricating photonic devices in bulk diamond, the low-contrast refractive index modulation induced by ion implantation, instead of merely being a side effect, could play an active role in a more effective device design [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-Vacancy (NV) defects in particular display particularly attractive characteristics due to their individual addressability, optical spin polarization and long coherence times, even at room temperatures [2,3]. The prospect of creating all-diamond integrated photonic structures has thus triggered interest in the possibility of fabricating optical waveguides [4] and other photonic structures [5] in diamond using ion implantation to modulate its refractive index. Moreover, an accurate control of refractive index variations is mandatory in all photonic applications which are based on ion implantation [6].…”
mentioning
confidence: 99%
“…Despite this, a surprisingly small number of publications in the literature have addressed the problem of the index of refraction variation in diamond with ion irradiation [7][8][9]. Following the first systematic studies of damage-induced refractive index variation at a fixed wavelength [10] and the demonstration of waveguide fabrication in diamond with ion implantation [4], the dependence of refractive index variation upon structural damage needs to be systematically explored in a wide wavelength range for a broader spectrum of ion species and energies. In this paper, we report on the use of Variable-Angle Spectroscopic Ellipsometry [11] (VASE) integrated with optical absorption measurement to assess refractive index and extinction coefficient variations as a function of damage density.…”
mentioning
confidence: 99%